The environmental performance of a building-integrated solar thermal collector, based on multiple approaches and life-cycle impact assessment methodologies. (May 2015) - Lamnatou, Chr.; Notton, G.; Chemisana, D.; Cristofari, C.
Abstract: In continuation of authors' previous study, the present investigation regards the comprehensive evaluation of the environmental profile of a patented building-integrated solar thermal collector, based on multiple Life Cycle Impact Assessment (LCIA) methodologies. The system has been developed and experimentally tested at the University of Corsica, in France and it consists of collectors integrated into building gutters. Three alternative configurations are examined by means of the LCIA methodologies Eco-Indicator 99 (EI99) and IMPACT 2002+ along with embodied energy and embodied carbon. Multiple approaches and scenarios are examined in order to evaluate the effect of several parameters on system environmental performance. The results, based on all the LCIA methodologies used, reveal that the configuration with collectors in parallel connection can considerably improve the environmental profile of the reference system (collectors in series). This impact can be further reduced by using systems with double absorber surface/output and/or recycling. On the other hand, the present investigation provides a critical comparison of the proposed system with other types of solar thermal and conventional heating systems. The primary energy and CO2 savings (per month) related with the production of energy by the proposed BI solar thermal systems, instead of using a conventional heating system, are also presented. Highlights: Building-integrated solar thermal collectors: analysis of the environmental profile. Multiple life-cycle impact assessment methodologies (eco-points, etc) are utilized. A sensitivity analysis is conducted; several scenarios and databases are examined. Configuration collectors-in-parallel greatly improves system environmental profile. The proposed system is compared with other solar thermal and conventional systems.